2011
DOI: 10.1080/14733145.2010.548563
|View full text |Cite
|
Sign up to set email alerts
|

Changes of attachment status among women with personality disorders undergoing inpatient treatment

Abstract: Background: Attachment has increasingly received attention in psychotherapy and has been used as a predictor of process and outcome. Studies investigating changes of attachment styles during psychotherapy are very rare. Method: Forty women with either borderline (BPD) or avoidant personality disorders (AVPD), treated as inpatients, were investigated using an attachment interview (interpersonal relations assessment (IRA)), and questionnaires to determine therapy outcome at the beginning and after seven weeks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
1
9
2
Order By: Relevance
“…The results of these two studies are in contrast to those obtained by Strauss et al (2011) in an inpatient sample using an interview measure. This may be due to the slightly shorter treatment duration used in the study by Strauss and colleagues and the additional complexity of this patient group (i.e., co-morbid borderline and avoidant personality disorder).…”
Section: Self-report Approachcontrasting
confidence: 80%
See 1 more Smart Citation
“…The results of these two studies are in contrast to those obtained by Strauss et al (2011) in an inpatient sample using an interview measure. This may be due to the slightly shorter treatment duration used in the study by Strauss and colleagues and the additional complexity of this patient group (i.e., co-morbid borderline and avoidant personality disorder).…”
Section: Self-report Approachcontrasting
confidence: 80%
“…Nevertheless, these results need to be interpreted with caution because of the lack of control over confounding variables. Strauss, Mestel, and Kirchmann (2011) demonstrated significant reductions in attachment security and increases in attachment avoidance over a 7-week program for female inpatients with Borderline Personality Disorder and Avoidant Personality Disorder using the AAPR. These findings are perhaps not surprising, however, given the short treatment period in relation to the complexity of needs of the patient group.…”
Section: Interview Approachmentioning
confidence: 98%
“…These results are consistent with previous research with BPD inpatients, which show that reductions in anxious attachment were more relevant to therapeutic outcomes than changes in avoidant attachment (Strauss, Mestel, & Kirchmann, 2011) and that anxious attachment and emotional dysregulation are particular struggles associated with BPD (Scott et al, 2013). The finding that anxious attachment was reduced in ways that affected psychiatric symptoms during DBT is noteworthy because attachment has not been part of DBT theory but is a central dimension of mentalization-based treatment, suggesting there may be potential for theoretical integration.…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies have confirmed the theorized relationship between AVPD and both anxious and avoidant strategies. 46 , 81 , 103 110 Using the four-category model of Bartholomew and Horowitz, 111 which posits that attachment may be classified into one of four groups determined by positive or negative views of the self and positive or negative views of others, some studies also identified a fearful attachment style in AVPD. 101 , 112 , 113 In the four-category model, the fearful attachment style may be the most disabling, since it is associated with negative views of both self and other.…”
Section: Toward An Understanding Of Etiological Factorsmentioning
confidence: 99%